Elementary School Students’ Readiness to Adopt Artificial Intelligence (AI)-Based Learning - Yulianti, Anggun; Andrijati, Noening; Wijayati, Nanik; Avrilianda, Decky (Gemilang Maju Publikasi Ilmiah (GMPI), 2026)
This research will focus on the evaluation of elementary school students' readiness to use AI for their learning process through three significant factors, namely dimensions of readiness, factors affecting readiness, and conditions for infrastructure and ecosystem of schools. The type of this research is a literature review that utilizes qualitative methods. This data collection is done based on ten scientific articles from national and international journals, sourced from the Google Scholar, Scopus, ERIC, and Sinta databases. The data were collected by documentation, and data analysis was done using content analysis and thematic synthesis. From the research findings, it is evident that the readiness for AI integration among primary level pupils entails three related constructs; cognitive (knowledge of AI), affective (attitudes, motivation, self-confidence), and behavioral (interaction skills with AI technologies). While internal variables (teacher attitudes, TPACK) strongly positively impact AI integration (β = 0.791), external variables (government policies, technological infrastructure, community involvement) indirectly impact AI usage via internal variables (β = 0.217). Less than a third of teachers (28%) currently adopt AI in teaching, whereas the majority (82%) stick to conventional instructional techniques. These results indicate that the readiness of students will not take place without ensuring the readiness of teachers and that both need to work in harmony with each other for internal capacity building and equal external support. The conclusion drawn from this study is that the level of readiness of elementary school students to adopt learning based on artificial intelligence has only started and that they are not consistent yet. The application of AI in elementary schools largely relies on enhancing teacher competencies, equal infrastructure, and developing policies that consider ethics, privacy, and social justice. More studies should be conducted concerning rural areas and tools to measure readiness in Indonesia.